Human psychological phenomena in science and islam: An islamic education values perspective - Ghina Hashunatil Mar’ah; Naeila Putri Ar-Romli; AnzarAquil (Yayasan Azhar Amanaa Yogyakarta, 2025)
The phenomenon of human psychology is an important aspect in understanding the existence and dynamics of human life. This article aims to examine the structure and function of the soul from the perspective of the Quran and to compare it with modern scientific views, especially psychology. The Quran depicts the soul as a spiritual entity that possesses the potential for both good and evil, which can develop towards inner tranquility (nafs muṭma’innah) or fall into moral corruption (nafs ammārah). The scientific approach through psychology explains the soul as the center of thinking, feeling, and acting processes. Using a descriptive-qualitative approach, this study finds common ground between the concepts of psychology in revelation and science, which mutually reinforce each other in explaining the essence of humans as physical and spiritual beings.